Sensitive method for the detection of mutagenic nitroarenes and aromatic amines: new derivatives of Salmonella typhimurium tester strains possessing elevated O-acetyltransferase levels - Watanabe, Masahiko; Ishidate, Motoi; Nohmi, Takehiko (Mutation Research/Environmental Mutagenesis and Related Subjects, 1990)
Acetyl-CoA: N-hydroxyarylamine O-acetyltransferase is an enzyme involved in the intracellular metabolic activation of arylhydroxylamines derived from mutagenic nitroarenes and aromatic amines. The acetyltransferase gene of Salmonella typhimurium TA1538 was cloned into pBR322 and the plasmids harboring the gene were introduced into TA98 and TA100. The resulting strains (YG1024 and YG1029) had about 100 times higher 2-hydroxyamino-6-methyldipyrido[1,2- a: 3′, 2′- d]-imidazole ( N-hydroxy-Glu-P-1) O-acetyltransferase activity than TA1538 containing pBR322, and were extremely sensitive to the mutagenic actions of 2-nitrofluorene, 1-nitropyrene, 1,8-dinitropyrene, 2-amino-6-methyldipyrido[1,2- a: 3′, 2- d]-imidazole (Glu-P-1), 2-aminofluorene and 2-aminoanthracene. These results indicate that the new strains permit the efficient detection of the mutagenicity of environmental nitroarenes and aromatic amines.